Local Administration of (−)-Epigallocatechin-3-Gallate as a Local Anesthetic Agent Inhibits the Excitability of Rat Nociceptive Primary Sensory Neurons - Syogo Utugi; Risako Chida; Sana Yamaguchi; Yukito Sashide; Mamoru Takeda (Cells)
While the impact of (−)-epigallocatechin-3-gallate (EGCG) on modulating nociceptive secondary neuron activity has been documented, it is still unknown how EGCG affects the excitability of nociceptive primary neurons in vivo. The objective of the current study was to investigate whether administering EGCG locally in rats reduces the excitability of nociceptive primary trigeminal ganglion (TG) neurons in response to mechanical stimulation in vivo. In anesthetized rats, TG neuronal extracellular single unit recordings were made in response to both non-noxious and noxious mechanical stimuli. Following the administration of EGCG, the mean firing rate of TG neurons to both non-noxious and noxious mechanical stimuli significantly decreased in a dose-dependent manner (1–10 mM), and both the non-noxious and nociceptive mechanical stimuli experienced the maximum suppression of discharge frequency within 5 min. These inhibitory effects lasted for approximately 20 min. These findings suggest that the local injection of EGCG into the peripheral receptive field suppresses the responsiveness of nociceptive primary sensory neurons in the TG, almost equal to that of the local anesthetic, 1% lidocaine. As a result, the local application of EGCG as a local anesthetic could alleviate nociceptive trigeminal pain that does not result in side effects, thereby playing a significant role in pain management.